THE URGENCY OF DEREGULATION TO MANIFEST A SINGLE NATIONAL EDUCATION SYSTEM AS MANDATED IN CONSTITUTION - Pandu Ario Bismo; Mandira Bienna Elmir; Ammalia Fitriah (IBLAM Law Review)
The Indonesian constitution imposes a mandate for the government to organize and manage a single national education system that shall be regulated by law (Article 31 paragraph (3)) in order to educate the life of the nation. As time goes by, Indonesia’s education regulation governance has deviated from that mandate. In reality, there are multiple Laws related to education in Indonesia. This circumstance has not only caused some difficulties for the stakeholders who want to understand the regulation, but also caused overlapping and hyperregulation. In this article, the Authors map out the problems in Indonesia’s education regulation policies and analyze the solutions. Deregulation by unifying all the Laws related to education should be considered in overcoming the hyperregulation. This research uses normative legal research method in exploring the relevant theories, histories, good practices, and options to manifest an effective education regulation governance as a single national education system.